2019
DOI: 10.3390/ijms20215362
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Measurable Residual Disease (MRD) in Hematopoietic Stem Cell Transplantation for Hematological Malignancies Focusing on Acute Leukemia

Abstract: The significance of measurable residual disease (MRD) in hematopoietic stem cell transplantation (HSCT) is well recognized in different hematological malignancies, but the evidence indicate that pre-transplant MRD status is of particular importance in acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML). In ALL, inadequate response at the level of MRD is a commonly accepted risk factor for relapse and thus an indication for allogeneic HSCT. Similarly, growing evidence from the literature strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 81 publications
1
27
0
1
Order By: Relevance
“…Thus, incorporating pretransplant MRD as an additional parameter in large transplant registry databases, though challenging, is of special importance. Accordingly, several reports from the ALWP of the EBMT have evidenced higher risk of relapse and worse transplantation outcomes in patients with detectable MRD at transplantation in various transplantation setting [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, incorporating pretransplant MRD as an additional parameter in large transplant registry databases, though challenging, is of special importance. Accordingly, several reports from the ALWP of the EBMT have evidenced higher risk of relapse and worse transplantation outcomes in patients with detectable MRD at transplantation in various transplantation setting [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“… 42‐44 . Given its strong independent predictive value, MRD assessment is recommended at various time points in treatment of AML patients, including that before proceeding to transplant 45,46 . In the absence of MRD assessment, our study has identified two useful clinical parameters—short duration of CR1 and presence of active disease—that may be useful to better select transplant candidates in a resource‐limited setting.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of MRD using multiparameter flow cytometry or real-time quantitative polymerase chain reaction or fluorescence in situ hybridization before transplant is associated with a high risk of relapse and inferior outcomes.. [42][43][44] Given its strong independent predictive value, MRD assessment is recommended at various time points in treatment of AML patients, including that before proceeding to transplant. 45,46 In the absence of MRD assessment, our study has identified two useful clinical parameters-short duration of CR1 and presence of active disease-that may be useful to better select transplant candidates in a resource-limited setting.…”
Section: Discussionmentioning
confidence: 99%
“…1). Оскільки бластні клітини -це незрілі клітини, які під час дозрівання перетворюються в функціональні клітини крові, то підвищений їхній рівень в КМ, після проведення курсу хіміотерапії, вказує на порушення процесів кровотворення -бластні клітини не дозрівають у функціонально-активні клітини крові [14,15].…”
Section: рис 2 розподіл дітей хворих на гостру лімфобластну лейкемію за частотою появи рецидивівunclassified